"Almost Bleeding to Death": The Conundrum of Acquired Amegakaryocytic Thrombocytopenia. (6th February 2014) - Brown, Gabrielle Elena; Babiker, Hani M.; Cantu, Carlos L.; Yeager, Andrew M.; Krishnadasan, Ravitharan
Abstract : Acquired amegakaryocytic thrombocytopenia (AAT) is a rare hematological disorder causing severe thrombocytopenia and bleeding. Previous in vitro studies postulated both cell-mediated suppression of megakaryocytopoiesis in early megakaryocytic progenitor cells and humoral-mediated suppression by anti-thrombopoietin antibodies as possible etiologies of AAT. Patients with AAT usually present with severe bleeding and thrombocytopenia that is unresponsive to steroids and intravenous immunoglobulin (IVIG). Although standard guidelines have not been established for management of AAT, a few case reports have indicated a response to immunosuppressive treatment. The prompt recognition of this disease entity is essential in view of the substantial risk of morbidity and mortality from excessive bleeding. We report a case of AAT successfully treated with equine antithymocyte globulin (ATG) and cyclosporine (CSP).